The interface morphology of diffusion bonded dissimilar stainless steel and medium carbon steel couples - Kurt, Bulent (Elsevier Science Sa, 2007)
In the present study, a duplex stainless steel and an austenitic stainless steel were diffusion bonded to medium carbon steel. The differences of two dissimilar metal couples at the test temperature on microstructural developments across the joint region were investigated. After diffusion bonding, microstructural analysis including metallographic examination, energy dispersive spectroscopy (EDS) and shear strength tests were performed. From the results, it was seen that mutual diffusion of C and Cr was effective on the morphology of the diffusion zone that affected the shear strength of the bonds. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: diffusion bonding; austenitic stainless steel; duplex stainless steel; medium carbon steel; interface morphology